Analysis of mixed convective heat transfer past an isoflux/isothermal sphere: influence of Prandtl number. (1st July 2020) - Raju, B Hema Sundar; Nath, Dipjyoti; Pati, Sukumar
Abstract: Numerical simulations are conducted to illustrate the influence of Prandtl number on the mixed convection heat transfer past an isoflux/isothermal sphere. A spherical geometry higher order compact scheme (SGHOCS) is applied to obtain the velocity and temperature fields. The results are demonstrated in terms of velocity, contours of vorticity, streamlines and isotherms together with drag coefficient ( C D ), local Nusselt number ( Nu ) and mean Nusselt number ( Nu ̄ ) on the surface of the sphere in the range of Reynolds number ( Re ) from 1 to 200, Prandtl number ( Pr ) from 0.72 to 20 and Richardson number ( Ri ) from 0 to 2.0. We identify the critical Richardson number ( Ri cr ) above which the flow separation is totally suppressed. The study reveals that for a particular value of Re, Ri cr increases with Pr for isoflux case, whereas the opposite trend is observed for an isothermal case. The drag coefficient decreases with Re and Pr, while the same increases with Ri . Furthermore, the drag coefficient is larger for isothermal boundary condition when compared to isoflux boundary condition. Intuitively, it is found that for higher values of Re and Pr, the variation of Nu ̄ with Ri is non-monotonic. Moreover, as Ri increases, the decrease in Nu ̄ is larger for isothermal boundary condition when compared to isoflux boundary condition.